The Prevalence of Strabismus and Associated Risk Factors in a Southeastern Region of Brazil - Schaal, Luisa Fioravanti [UNESP]; Schellini, Silvana Artioli [UNESP]; Pesci, Leonardo Toledo [UNESP]; Galindo, Alicia; Padovani, Carlos Roberto; Corrente, Jose Eduardo (Taylor & Francis, 2018)
Purpose: To determine the prevalence of strabismus and associated risk factors in southeastern Brazil. Methods: A cross-sectional, population-based study using a systematic sample from nine municipalities in a southeastern region of Brazil composed of 1852 individuals aged ≥1 and ≤12 years old was done. Visual acuity (VA), ocular alignment, and refractive error (RE) were evaluated. Strabismic individuals (strabismus group) were compared to orthotropic individuals (orthotropic group) to analyze risk factors linked to heterotropias. Results: Prevalence of strabismus was 0.81% in this population. In the strabismus group, we found 40% with hyperopia, 6.67% with astigmatism, 3.33% with myopia, 6.67% with amblyopia, and 8.33% with moderate anisometropia. In the orthotropic group, 6.85% had hyperopia, 18.12% astigmatism, 14.82% myopia, 0.19% amblyopia, and 4.37% moderate anisometropia. Conclusion: The prevalence of strabismus in southeastern Brazil was 0.81%. Strabismic individuals had more hyperopia. Amblyopia and moderate anisometropia were associated with strabismus.
Keywords: Amblyopia; anisometropia; orthotropias; refractive errors; squint